Reduced graphene oxide-multiwalled carbon nanotubes hybrid film with low Pt loading as counter electrode for improved photovoltaic performance of dye-sensitised solar cells - Suriani, A. B.; Muqoyyanah, M.; Mohamed, A.; Othman, M. H. D.; Mamat, M. H.; Hashim, N.; Ahmad, M. K.; Nayan, N.; Abdul Khalil, H. P. S. (Springer, 2018)
In this work, the role of reduced graphene oxide (rGO) with hyperbranched surfactant and its hybridisation with multiwalled carbon nanotubes (MWCNTs) and platinum (Pt) nanoparticles (NPs) as counter electrode (CE) were investigated to determine the photovoltaic performance of dye-sensitised solar cells (DSSCs). Sodium 1,4-bis(neopentyloxy)-3-(neopentyloxycarbonyl)- 1,4-dioxobutane-2-sulphonate (TC14) surfactant was utilised as dispersing and stabilising agent in electrochemical exfoliation to synthesise graphene oxide (GO) as initial solution for rGO production prior to its further hybridisation and fabrication as thin film. A chemical reduction process utilising hydrazine hydrate was conducted to produce rGO due to the low temperature process and water-based GO solution. Subsequently, hybrid solution was prepared by mixing 1 wt% MWCNTs into the produced rGO solution. TC14-rGO and TC14-rGO_MWCNTs hybrid solution were transferred into fluorine-doped tin oxide substrate to fabricate thin film by spraying deposition method. Finally, the CE films were prepared by coating with thin Pt NPs. Photoanode film was prepared by a two-step process: hydrothermal growth method to synthesise titanium dioxide nanowires (TiO2 NWs) and subsequent squeegee method to apply TiO2 NPs. According to solar simulator measurement, the highest energy conversion efficiency (η) was achieved by using CE-based TC14-rGO_MWCNTs/Pt (1.553%), with the highest short current density of 4.424 mA/cm2 . The highest η was due to the high conductivity of CE hybrid film and the morphology of fabricated TiO2 NWs/TiO2 NPs. Consequently, the dye adsorption was high, and the photovoltaic performance of DSSCs was increased. This result also showed that rGO and rGO_MWCNTs hybrid can be used as considerable potential candidate materials to replace Pt gradually.